Prevalence and Associated Factors of Psychosocial Impact of COVID-19 Pandemic among different population groups in Lahore, Pakistan: a cross-sectional study - Kiran Fatima, Nazia Mir, Sundus Fatima, Hassan Ali, Saadia Ch (Pakistan Journal of Medical & Health Sciences, 2022)
Background: COVID-19 pandemic presents a consequential threat to individual’s mental health in addition to obvious health-related impact. Aim: To focus on prevalence as well as related factors of psychosocial impact of COVID-19 in Lahore, Pakistan. Methods: Our study design was analytical cross-sectional, and study population comprised 382 participants including healthcare workers, teachers, students, and household members. We used non-probability convenience sampling method. We built a structured self-administered questionnaire for collection of data and psychological impact was measured with Impact of Event Scale-Revised (IES-R). Results: Independent factors related to psychological impact were identified using bivariate logistic regression and all significant factors at p-value 0.25 were processed using multivariate model. AORs with 95% CIs were used to assess magnitudes of associations. Prevalence of psychological impact in Pakistan is 53.4%. Being female (β=1.517; AOR=4.561; 95%CI: 2.838-7.329)and covering mouth when coughing and sneezing (β=0.486; AOR=1.626; 95%CI: 1.012-2.612)are significantly associated with psychosocial impact after logistic regression. Prevalence of psychological impact in Pakistan is very high. Conclusion: Henceforth, policy makers need to consider psychological issues while planning pandemic-related interventions.